Taxonomic novelties in Buchnera (Orobanchaceae) in Central and East Africa (Rwanda, Burundi, Democratic Republic of the Congo, Tanzania) - Fischer, Eberhard (Phytotaxa, 2025)
Two new species of Buchnera, B. schaijesii and B. nudicaulis from D.R. Congo, are described. The name Buchnera butayei, based on an illegitimate name published by De Wildeman, is validated. A lectotype for Buchnera keilii is designated. B. subcapitata is the older name for B. cryptocephala. For the latter species, a lectotype and an epitype are designated.